Does it matter if those who matter don't mind? Effects of gang versus delinquent peer group membership on labeling processes - Buchanan, Molly (Criminology, 2020)
Despite renewed interests in the labeling perspective and the impact of official intervention on individuals’ future outcomes, scant attention has been given to potential conditioning factors for theorized labeling processes. We argue that, when viewed through a symbolic interactionist lens, variations in the nature of primary social groups, through which individuals filter official labels like arrest, may generate patterns for subsequent self-concept and delinquency that are contrary to what labeling theory indicates. To test our rationale, we offer a moderated mediation model in which gang membership is expected to differentially impact the effect of arrest on future delinquency through an intermediary mechanism: self-esteem. We test a gang-nongang dichotomy and then probe further to test whether hypothesized effects are gang specific or occur similarly for nongang youths with highly delinquent peer groups. Analyzed using Rochester Youth Development Study (RYDS) data (N = 961), comparisons between gang members and nonaffiliated youths with similarly highly delinquent peer groups revealed no significant differences in conditional indirect effects of arrest on self-esteem and future delinquency; the two groups were similarly insulated from any negative impact of arrest on self-esteem. For nongang youths with fewer delinquent peers, however, arrest significantly reduced later self-esteem, which in turn increased their future delinquency.